10.1142/9789814343060 (CrossRef Listing of Deleted DOIs, 2000)
Colorectal cancer (CRC) frequently develops resistance to 5-fluorouracil (5-FU)-based chemotherapy, which remains a major obstacle to successful treatment. Ginseng-containing Sijunzi Decoction (SJZD), a classical Traditional Chinese Medicine formula, has demonstrated antitumor activity; however, whether and how SJZD enhances 5-FU sensitivity remains largely unclear. In this study, SJZD-containing serum was prepared and administered to 5-FU-resistant CRC cell lines (HCT116/5-FU and SW480/5-FU). Chemosensitivity was evaluated using Cell Counting Kit-8 (CCK-8) and Calcein-AM/propidium iodide (PI) staining assays, while ferroptosis was assessed by measuring oxidative stress-related indicators, including malondialdehyde (MDA), glutathione (GSH), reactive oxygen species (ROS), and intracellular ferrous iron (Fe[Formula: see text]) levels. In addition, a BALB/c nude mouse xenograft model was established to validate the synergistic antitumor effects of SJZD and 5-FU in vivo. Protein-protein interactions and ubiquitination were examined by co-immunoprecipitation and in vitro ubiquitination assays. Our results demonstrated that SJZD markedly enhanced the sensitivity of resistant CRC cells to 5-FU by inhibiting cell proliferation and promoting ferroptosis both in vitro and in vivo. In the xenograft model, combined treatment with SJZD and 5-FU produced significantly greater reductions in tumor volume and tumor weight than treatment with 5-FU alone. Furthermore, the ferroptosis inhibitor ferrostatin-1 (Fer-1) effectively abolished the chemosensitizing effect of SJZD, indicating that ferroptosis is required for SJZD-mediated reversal of 5-FU resistance. Mechanistically, SJZD suppressed the expression of the E3 ubiquitin ligase membrane-associated ring finger protein 3 (MARCHF3), thereby inhibiting the ubiquitination and proteasomal degradation of arachidonate 15-lipoxygenase (ALOX15), a critical regulator of ferroptosis. Rescue experiments further demonstrated that ALOX15 silencing or MARCHF3 overexpression significantly attenuated SJZD-induced ferroptosis and reversed its sensitizing effect on 5-FU-resistant CRC cells. Collectively, these findings demonstrate that SJZD enhances the chemosensitivity of CRC cells to 5-FU by activating ferroptosis through regulation of the MARCHF3/ALOX15 axis. This study provides mechanistic insight into the antitumor activity of SJZD and highlights its potential as a promising adjuvant strategy for overcoming 5-FU resistance in CRC.